In vitro comparative evaluation of Tamarix gallica extracts for antioxidant and antidiabetic activity. Issue 3 (February 2023) - Nisar, Jaweria; Ali Shah, Syed Muhammad; Ayaz, Sultan; Akram, Muhammad; Rashid, Abid; Mustafa, Imtiaz; Nisar, Zonaira
Tamarix gallica known as Jhau is traditionally used as expectorant, liver tonic, laxative, astringent, and antidiarrheal. The current study was proposed to determine the in vitro antioxidant, antidiabetic properties of the methanolic, ethanolic, and aqueous extracts of Tamarix gallica arial part, subsequently the phytochemical evaluation. Hence, Tamarix gallica arial part extracts were extracted with methanol (MthTg), ethanol (EthTg), and distilled water (AqTg). Extracts phytochemical analysis were accomplished to identify the phenolic components (TPC and TFC). Extracts antioxidant property was evaluated by DPPH, FRAP, and ABTS assay. For antidiabetic property, α-amylase and α-glucosidase inhibitory activities were assessed. One Way ANOVA was applied statistically by means of software SPSS Statistics 23 and attained data were definite as mean ± standard deviation. Result revealed that EthTg have the maximum TPC and TFC levels than MthTg and AqTg. Antioxidant property in relations of DPPH (lowest IC50  = 1.309 ± 0.31), FRAP (323.51 ± 2.32), and ABTS (266.97 ± 25.14) assay was also highest in EthTg. EthTg was also exposed highest α-amylase and α-glucosidase inhibition activity with lower IC50 (1.116 ± 0.051; 0.402 ± 0.2, respectively). The extracts antioxidant and antidiabetic activities order was as EthTg > MthTg > AqTg. TFC and TPC also revealed directly proportional correlation with antioxidant, and antidiabetic properties of the Tamarix gallica arial part extracts. Results noticeably stated that the ethanolic extract of Tamarix gallica have the highest antioxidant and antidiabetic properties. Tamarix gallica has competency to reduce the oxidative stress and can be utilized in the management of diabetes.